Evaluating the impact of psychological entitlement on cyberloafing: the mediating role of perceived organizational justice. Issue 1 (2nd November 2020) - Rahaei, Arefeh; Salehzadeh, Reza
Abstract : Purpose: The purpose of this study is to evaluate the impact of psychological entitlement and perceived organizational justice on cyberloafing. Design/methodology/approach: In this study, a cross-sectional research design based on a questionnaire method was used to collect the required data from a sample of 226 employees working at selected universities in the city of Isfahan, Iran. To test the research hypotheses, structural equation modeling was used. Findings: According to the findings, psychological entitlement could have a significant impact on perceived organizational justice and consequently perceived organizational justice could significantly influence cyberloafing. Moreover, psychological entitlement could significantly influence cyberloafing and finally, psychological entitlement could have a significant effect on cyberloafing through perceived organizational justice. Originality/value: This research provides valuable insight for studying the relationship among psychological entitlement, perceived organizational justice and cyberloafing.